2018
DOI: 10.1007/s12371-018-0320-1
|View full text |Cite
|
Sign up to set email alerts
|

First Paleo-Fairy Chimney Findings in the Cappadocia Region, Turkey: a Possible Geomorphosite

Abstract: Fairy chimneys are conical, columnar, and mushroom-like erosional landforms sometimes exceeding 10 m in height and width that developed on ignimbrite layers in the Cappadocia region of Central Anatolia Volcanic Province. These fairy chimneys, and troglodytes carved into the ignimbrites during the Roman, Seljuk, and Ottoman eras, have turned Cappadocia into a worldrenowned site. While there are at least 10 different thick ignimbrite members in Cappadocia, fairy chimneys developed extensively on the Kavak, Zelve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 36 publications
(98 reference statements)
0
10
0
Order By: Relevance
“…These recent findings invalidated some previous views on the river drainage system (Doğan, 2011;Koçyiğit and Doğan, 2016) but supported others (Doğan et al, 2019a). For example, Doğan (2011), and Koçyiğit and Doğan (2016) suggested that the drainage system of the Kızılırmak River was formed after the Valibaba Tepe ignimbrite emplacement.…”
Section: Revised Stratigraphies Of the üRgüp Formation And Kızılırmak River Terracesmentioning
confidence: 81%
See 2 more Smart Citations
“…These recent findings invalidated some previous views on the river drainage system (Doğan, 2011;Koçyiğit and Doğan, 2016) but supported others (Doğan et al, 2019a). For example, Doğan (2011), and Koçyiğit and Doğan (2016) suggested that the drainage system of the Kızılırmak River was formed after the Valibaba Tepe ignimbrite emplacement.…”
Section: Revised Stratigraphies Of the üRgüp Formation And Kızılırmak River Terracesmentioning
confidence: 81%
“…According to previous studies (Doğan, 2010(Doğan, , 2011Koçyiğit and Doğan, 2016;Doğan et al, 2019a), the Kızılırmak River drainage system was formed over the Ürgüp Formation at the beginning of Quaternary with the end of the extensional regime and start of a strikeslip neotectonic regime. Tectonic studies revealed that the river settled in the Avanos and Salanda strike-slip fault zones during the Quaternary (Koçyiğit and Doğan, 2016).…”
Section: Geological and Geomorphological Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…12). Around Selime and southward to Yaprakhisar, the Cemilköy ignimbrite is deeply incised by numerous rills and gullies forming the typical Cappadocian landscape made of "fairy chimneys" in a badland landscape (Beekman 1966;Sarıkaya et al 2015;Çiner and Aydar 2019;Doğan et al 2019). The characteristic fairy chimneys are also well developed in the thick tuff wall between Selime and Yaprakhisar on the right bank of the Melendiz River (Fig.…”
Section: Formation and Evolution Of Melendiz River Valley During Quatmentioning
confidence: 99%
“…b Annual precipitation map of Turkey (modified from Atalay 1983). c Location map of the study area et al 2015a; Çiner and Aydar 2019;Doğan et al 2019;Mouralis et al 2019), its Neogene-Quaternary geology has not been considered as a whole with its both depositional environments and biota. The mentioned studies were mainly focused on dating of volcanic-pyroclastic units and geomorphic features, and not interested to outline the paleoenvironmental evolution of the region except a few studies dealing with Neogene and Quaternary (e.g., middle Miocene- Akgün et al 1995; late Miocene-Pliocene-Le Pennec et al 2005;Ocakoğlu 2004; late Pleistocene- Türkecan et al 2004).…”
Section: Introductionmentioning
confidence: 99%